Pemberian Edukasi Ayah dalam Upaya Peningkatan Keberhasilan Menyusui Di PMB Eliyanti, Kabupaten Kuningan - Mariani, Nina Nirmaya; Suratmi, Suratmi (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2021)
Breast milk (ASI) is the best food for babies during the first 6 months of their life because breast milk provides essential nutrients for infant growth and development. The facts in the real life are that the exclusive breastfeeding program has not been able to run as expected. The husband's role in breastfeeding will be successful if it is based on knowledge of the importance of breastfeeding. This community service aims to increase the coverage of breastfeeding so that every baby can achieves the normal stages of growth and development. The target in this community service activity is fathers who have babies aged 0-6 months in the work area of PMB Eliyanti, Amd.Keb, Kuningan Regency. The method of implementation is face-to-face and discussions using health protocols, either in groups or individually. The class of pregnant women so that the father can support the success of breastfeeding. The result of this activity is the increasing in knowledge both about breastfeeding and the role of fathers. It is hoped that the father can be involved in the program.